A Fragile Power : Scientists and the State - Mukerji, Chandra (Princeton : Princeton University Press, 2014)
When the National Science Foundation funds research about the earth's crust and the Department of Energy supports studies on the disposal of nuclear wastes, what do they expect for their money? Most scientists believe that in such cases the government wants information for immediate use or directions for seeking future benefits from nature. Challenging this oversimplified view, Chandra Mukerji depicts a more complex interdependence between science and the state. She uses vivid examples from the heavily funded field of oceanography, particularly from recent work on seafloor hot springs and o.
Directing Scientific DiscourseCHAPTER TEN ; The Voice of Science; Notes; Bibliography; Index.
Print version record.
Cover; Contents; Preface.
eBooks on EBSCOhost
Keywords: Science -- Social aspects -- United States; Science and state -- United States; Research -- United States -- Finance; Federal aid to research -- United States; Politique scientifique et technique -- États-Unis.; Sciences -- Aspect social -- États-Unis.; SCIENCE -- History; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Federal aid to research; Research -- Finance; Science and state; Science -- Social aspects; United States